tom2342344 | *about how |

csko | TRWBW: im trying to understand what you say tryied to solve that equation system with no success |

TRWBW | csko: well the two operations are analgous to the gcd operations, and it terminates when you get some final f'=d |

frobozz_ | don't you mean the euclidean algorithm for gcd? |

TRWBW | frobozz_: i do |

csko | i think i know what you are talking about now |

TRWBW | csko: really they alternate, so you could just make it f'=1/(1+(b-a)/a)) |

albacker | guys n/(n+2) - (1-n)/(1+n) is positive or negative for n>=0 |

TRWBW | albacker: do it out, just like any other fraction subtraction |

johnDoe2 | It has the same sign als n(n+1)-(1-n)(n+2) |

csko | positive for n>-1/2+1/2*5^(1/2) |

johnDoe2 | Therefore it's possitive |

csko | for 0 its -1 |

johnDoe2 | The term is negative only for n=1. And positive for all n greater than 0 for n=0* |

de1337 | @mbot: 2+2 |

mbot | de1337: 4 |

de1337 | @mbot: 1/2(E^(I*14) + E^(-I*14)) // N |

mbot | de1337: 0.1367372182078336 + 0.*I |

de1337 | @mbot: Cos[14] //N |

mbot | de1337: 0.1367372182078336 |

spaceinvader | mbot: % Solve[x^2-2x-5==0,x] @mbot: % Solve[x^2-2x-5==0,x] |

mbot | spaceinvader: {{"No state is preserved between computations, so % doesn't work."*(x -> 1 - Sqrt[6])}, {"No state is preserved between computations, so % doesn't work."*(x -> 1 + Sqrt[6])}} |

frobozz_ | @mbot: 4*atan[1] |

mbot | frobozz_: 4*atan[1] |

spaceinvader | @mbot: % Solve[x^2-2*x-5==0,x] |

mbot | spaceinvader: {{"No state is preserved between computations, so % doesn't work."*(x -> 1 - Sqrt[6])}, {"No state is preserved between computations, so % doesn't work."*(x -> 1 + Sqrt[6])}} |

spaceinvader | @mbot: Solve[x^2-2*x-5==0,x] |

mbot | spaceinvader: {{x -> 1 - Sqrt[6]}, {x -> 1 + Sqrt[6]}} |

frobozz_ | @mbot: 4*Atan[1] |

spaceinvader | hah |

mbot | frobozz_: 4*Atan[1] |

frobozz_ | ugh. |

de1337 | @mbot: 4*ArcTan[1] //N |

mbot | de1337: 3.141592653589793 |

de1337 | @mbot: 4*ArcTan[1] == Pi |

mbot | de1337: True |

spaceinvader | @mbot: Solve[(2+Sqrt[3](5-Sqrt[3]== a + b Sqrt[3],ab] |